Review of Dasyrhopala Jordan, 1904 (Coleoptera: Anthribidae) with description of three new species from Brazil - Vilhena, Poliana De Mesquita; Mermudes, José Ricardo Miras (Zootaxa, 2025)
The genus Dasyrhopala Jordan, 1904 (Anthribinae: Discotenini Lacordaire, 1865) is reviewed and three new species from Brazil are described: Dasyrhopala tarsinivea Vilhena & Mermudes sp. nov. from Corupá-Santa Catarina; Dasyrhopala trimellina Vilhena & Mermudes sp. nov. from Barra de São Francisco-Espírito Santo; and Dasyrhopala thapsinogutta Vilhena & Mermudes sp. nov. from Sooretama-Espírito Santo. All species come from the endangered Atlantic Forest biome, located in the southeast, south, and parts of the northeast of Brazil. A key to the now four known species of Dasyrhopala is provided and genitalia are described and illustrated for the first time. New insights into the morphology, mainly of terminalia, and geographic distribution of the genus are provided.